Is arsenic a major determinant of health aid disbursement? An evaluation with a Tobit model and challenges in Cambodia - Jinhwan Oh; Seunghee Lee (Development Studies Research, 2023)
ABSTRACTAlthough arsenic contamination was originally considered an environmental problem, its impact on human beings is now widely deemed a serious health issue. This study examines whether international communities perceive arsenic as a health issue and discusses current challenges regarding arsenic contamination in Cambodia. Using comprehensive panel data covering 122 health aid recipient countries across three-plus decades (1990–2020), the first part of our study finds that the recipients’ health needs caused by major incidences (HIV, tuberculosis, and malaria) are all important factors determining health aid. However, health aid is conditionally effective on countries with high arsenic contamination when they have a better governance level. In this context, we conduct a case study focusing on Cambodia, where arsenic contamination is quite serious but given less attention than in other countries. In Cambodia, both inter-governmental coordination and coordination among international organizations are weak, and no long-term blueprint for arsenic mitigation has yet been developed. To fundamentally and sustainably address this problem, we suggest that Cambodia establish a control tower incorporating government, research institutes, and international agencies.